2022
DOI: 10.1002/hyp.14480
|View full text |Cite
|
Sign up to set email alerts
|

Can gravel augmentation restore thermal functions in gravel‐bed rivers? A need to assess success within a trajectory‐based before–after control–impact framework

Abstract: Gravel augmentation has become common practice to mitigate the effects of decline in upstream sediment supply in gravel‐bed rivers. However, the functional aspects of river systems are often left out of rehabilitation monitoring programmes. Despite temperature being a fundamental parameter determining the general health of rivers, a limited number of studies have tested whether gravel augmentation can aid restoring thermal functions. Using airborne thermal infrared (TIR) imagery, this paper explores potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Armored and clogged streambed sediment (i.e., the erosion-resistant layer of relatively large particles that is established on the surface of the streambed through the removal of finer particles by stream flow) can also impact CWPs by limiting water exchange with groundwater (Wawrzyniak et al, 2016) and reducing groundwater discharge points that can dry out when the water table level lowers as a result of channel incision from mining, logging, grazing, channel straightening, and sediment starvation (Marteau et al, 2022).…”
Section: Hydrology and Geomorphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Armored and clogged streambed sediment (i.e., the erosion-resistant layer of relatively large particles that is established on the surface of the streambed through the removal of finer particles by stream flow) can also impact CWPs by limiting water exchange with groundwater (Wawrzyniak et al, 2016) and reducing groundwater discharge points that can dry out when the water table level lowers as a result of channel incision from mining, logging, grazing, channel straightening, and sediment starvation (Marteau et al, 2022).…”
Section: Hydrology and Geomorphologymentioning
confidence: 99%
“…Cold‐water patches fully mix with ambient water at high streamflow in rivers draining large stratified natural lakes that show abrupt wind‐driven drops in river temperature, leading to the loss of discrete CWPs (Lisi & Schindler, 2015) and a reduction in CWRs. Armored and clogged streambed sediment (i.e., the erosion‐resistant layer of relatively large particles that is established on the surface of the streambed through the removal of finer particles by stream flow) can also impact CWPs by limiting water exchange with groundwater (Wawrzyniak et al, 2016) and reducing groundwater discharge points that can dry out when the water table level lowers as a result of channel incision from mining, logging, grazing, channel straightening, and sediment starvation (Marteau et al, 2022).…”
Section: State Of the Sciencementioning
confidence: 99%
“…For instance, in climate change studies the focus has been on attributing human activities to observed long-term changes in climate parameters (surface temperature, precipitation, circulation), as well as extreme events (storms, hurricanes, heat waves) (Zhai et al, 2018). Similarly, in ecological monitoring studies, the search for the quantification of environmental impacts lead to the development of the Before-After-Control-Impact (BACI) design, considered to be a statistically powerful experimental design for environmental impact research (Underwood, 1992;Smokorowski and Randall, 2017) and that is being increasingly applied in fluvial geomorphology (see recent work by Marteau et al, 2022).…”
Section: Advantages and Limitations Of A Hypothesis-driven Approach F...mentioning
confidence: 99%
“…A BACI (Before-After-Control-Impact) approach is classically used to assess the effects of river restoration actions (Marteau et al, 2022) but can be appropriate to assess the unit-effect of any driver of change. It relies on the comparison with a "pre-" state (Before), (e.g., before the construction of the Plan d'Arem dam), and with a reach out of the zone of influence of the considered pressure (Control), (e.g., upstream the Plan d'Arem dam).…”
Section: A Trajectorial Before-after-control-impact (Baci) Approach T...mentioning
confidence: 99%